2020
DOI: 10.1002/jbmr.4507
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Responsive Gene MAST4 Regulates Myeloma Bone Disease

Abstract: Our previous data showed that young female multiple myeloma (MM) patients had a low frequency of osteolytic lesions. Based on this clinical observation, we found that estrogen cell signaling played a regulatory role in MM bone disease (MMBD), and the estrogen‐responsive gene microtubule‐associated serine/threonine kinase family member 4 (MAST4) was a critical factor. The presence of estrogen in cell cultures promoted MAST4 expression in MM cells, while knocking down estrogen receptor 1 (ESR1) inhibited MAST4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The search for estrogen response genes revealed, among others, MAST4. The study further showed that MAST4 is a negative regulator of MMBD and that the levels of MAST4 in MM cells negatively correlate with the severity of MMBD; high estrogen pathway activation levels correlated with high levels of MAST4 [30]. Pathway analyses suggested that MAST4 regulates the PI3-Kinase and mTOR pathways and that MAST4 colocalizes and co-immunoprecipitates with PTEN in MM cells.…”
Section: Association Of Mast Kinase Mutations In Cancermentioning
confidence: 77%
See 2 more Smart Citations
“…The search for estrogen response genes revealed, among others, MAST4. The study further showed that MAST4 is a negative regulator of MMBD and that the levels of MAST4 in MM cells negatively correlate with the severity of MMBD; high estrogen pathway activation levels correlated with high levels of MAST4 [30]. Pathway analyses suggested that MAST4 regulates the PI3-Kinase and mTOR pathways and that MAST4 colocalizes and co-immunoprecipitates with PTEN in MM cells.…”
Section: Association Of Mast Kinase Mutations In Cancermentioning
confidence: 77%
“…Phosphorylation of the carboxy-terminal domain of PTEN reduces its activity and prevents PTEN from degradation, suggesting that MAST2 regulates PTEN activity and stability in vivo [29]. This MAST kinase-dependent inhibition of PTEN activity was also observed in multiple myeloma cell lines, where knockdown of MAST4 leads to reduced PTEN activity and increased activity of proteins involved in the mTOR signaling pathway [30]. The PTEN/MAST2 interaction might also play an important role in neuronal homeostasis.…”
Section: Substrates and Interactors Of Mast Kinasesmentioning
confidence: 88%
See 1 more Smart Citation
“…Estrogen signaling negatively regulates multiple myeloma-associated bone lesions through MAST4. The reason behind this is the regulation of the PI3-kinase and mTOR pathways by MAST4 [16]. Underexpression of MAST4 is associated with survival in breast cancer patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…MAST4 is a large protein (∼265 kD); it comprises 2,434 amino acids and encompasses a DUF1908, a serine/threonine kinase, and a post-synaptic density-95/disks large/zonula occludens-1 (PDZ) domain. MAST4 has several reported functions in neuroprotection, spermatogenesis, the progression of multiple myeloma bone disease, and cell fate determination of mesenchymal stromal cells in bones and cartilages ( Gongol et al, 2017 ; Lee et al, 2021 ; Cui et al, 2022 ; Kim et al, 2022 ). In this study, we describe the ciliary localization of MAST4 and the physical and functional interactions between MAST4 and Tctex-1 in ciliary resorption.…”
Section: Introductionmentioning
confidence: 99%